2017
DOI: 10.1051/0004-6361/201730643
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for two-loop interaction from IRIS and SDO observations of penumbral brightenings

Abstract: Aims. We investigate small scale energy release events which can provide clues on the heating mechanism of the solar corona. Methods. We analyzed spectral and imaging data from the Interface Region Imaging Spectrograph (IRIS), images from the Atmospheric Imaging Assembly (AIA) aboard the Solar Dynamics Observatoty (SDO), and magnetograms from the Helioseismic and Magnetic Imager (HMI) aboard SDO. Results. We report observations of small flaring loops in the penumbra of a large sunspot on July 19, 2013. Our mai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
2
8
0
Order By: Relevance
“…Here we focus on the observed morphology of the AIA 94 Å and 131 Å hot emission in each of these IRIS events, which suggests that the impulsive heating derives from large scale magnetic rearrangements/large angle reconnection. The interaction of small loops has been taken as explanation of a small flare observed with IRIS (Alissandrakis et al 2017), and our study provides direct evidence from the morphology observed in the hot AIA channels counterparts. Many recent papers have studied simultaneous observations from IRIS and SDO/AIA to investigate magnetic rearrangements causing localized brightenings in the transition region, and likely related with flux emergence (e.g., Jiang et al 2015;Toriumi et al 2017;Guglielmino et al 2018;Huang 2018;Tian et al 2018;Guglielmino et al 2019).…”
Section: Discussionsupporting
confidence: 65%
“…Here we focus on the observed morphology of the AIA 94 Å and 131 Å hot emission in each of these IRIS events, which suggests that the impulsive heating derives from large scale magnetic rearrangements/large angle reconnection. The interaction of small loops has been taken as explanation of a small flare observed with IRIS (Alissandrakis et al 2017), and our study provides direct evidence from the morphology observed in the hot AIA channels counterparts. Many recent papers have studied simultaneous observations from IRIS and SDO/AIA to investigate magnetic rearrangements causing localized brightenings in the transition region, and likely related with flux emergence (e.g., Jiang et al 2015;Toriumi et al 2017;Guglielmino et al 2018;Huang 2018;Tian et al 2018;Guglielmino et al 2019).…”
Section: Discussionsupporting
confidence: 65%
“…Direct evidence includes the detection of time variability of the intensity A&A 638, A62 (2020) (e.g., Berghmans et al 1998) or the emission measure (e.g., of clusters of pixels above some predefined threshold. In most studies, most of the detected events are spatially unresolved (e.g., Benz & Krucker 1999), but some events may exhibit a loop-like morphology (e.g., White et al 1995;Warren et al 2007), a jet-like morphology (e.g., Tian et al 2014;Alissandrakis et al 2015), show evidence of two-loop interactions (e.g., Shimizu et al 1994;Alissandrakis et al 2017a), or even resemble Ellerman bombs (e.g., Shetye et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It has also observed that interaction between cool transition region loops could result in heating and then forming hotter coronal loops (e.g. Alissandrakis et al 2017;Yan et al 2018;Chitta et al 2018).…”
Section: Introductionmentioning
confidence: 99%